OXIDATIVE METABOLISM AND PHYSICAL PROPERTIES OF THE BLOOD IN ATHLETES - MARTUSEVICH, ANDREW K; A KARUZIN, KONSTANTIN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: Monitoring of metabolic status in athletes includes a wide range of different parameters, but not all of them have been fully studied. Thus, the presence of oxidative stress is noted in athletes, but its features are revealed only in fragments. The crystallogenic properties of blood in athletes have not been previously studied. Methods: The study enrolled a total of 262 athletes (19–29 years old) that are highly qualified in cyclic sports. Furthermore, screening data of apparently healthy non-exercising volunteers of the same age (n=35) were used for control. Blood serum of the athletes and non-exercising volunteers was analyzed for 8-isoprostane level, oxidized low-density lipoproteins, activity of superoxide dismutase, and glutathione peroxidase and reductase. We also studied the level α- and β-carotenes, α- and γ-tocopherols, lycopene, lutein, and zeaxanthin. Crystallogenic properties of blood serum were tested with own method. Results: The complex study demonstrated the presence of shifts in oxidative metabolism and blood serum physical and chemical properties induced by professional sports and manifested both in the status of blood pro- and antioxidative systems and in shifts of biofluids crystallogenic activity. At the same time, the obtained data confirmed the development of oxidative stress in qualified athletes. Conclusion: Our data shown that there are some shifts of oxidative metabolism and crystallogenic properties of blood plasma in professional athletes.